2010
DOI: 10.1177/0885328209356328
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Bone Marrow Stromal Cells into Osteoblasts in a Self-assembling Peptide Hydrogel: In Vitro and In Vivo Studies

Abstract: A prerequisite of tissue engineering approaches with regard to autograft is a suitable scaffold that can harbor cells and signals. Conventionally, such scaffolds have been prepared as 3D scaffolds prefabricated from synthetic or natural biomaterials. RAD16 has been introduced as a new biomaterial, where synthetic peptides self-assemble to form a hydrogel. In this study, RAD16 was examined in terms of osteogenic efficacy and feasibility of ectopic mineralization. Two hundred and seventy-one RAD16 was cocultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Interestingly, scaffolds composed of SApeptides are able to induce adhesion and proliferation of differentiated cells and also to guide cell differentiation of stem cells. Ozeki M et al suggested that RAD16, a self-assembling ionic complementary peptide, serves as a matrix for osteogenic differentiation of cocultured bone marrow cells in vitro and in vivo [26]. On the negative side, hydrogels of SA-peptides have relatively modest moduli of up to about 10 kPa, and thus find application as injectable scaffolds for the treatment of small defects rather than as patches for large ones.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, scaffolds composed of SApeptides are able to induce adhesion and proliferation of differentiated cells and also to guide cell differentiation of stem cells. Ozeki M et al suggested that RAD16, a self-assembling ionic complementary peptide, serves as a matrix for osteogenic differentiation of cocultured bone marrow cells in vitro and in vivo [26]. On the negative side, hydrogels of SA-peptides have relatively modest moduli of up to about 10 kPa, and thus find application as injectable scaffolds for the treatment of small defects rather than as patches for large ones.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, scaffolds made of SAPs support adhesion and proliferation of differentiated cells and also stimulate cell differentiation of immature stem cells [ 11 ]. However, since SAP hydrogels are characterized by a relatively low amount of moduli (up to about 10 kPa), they have mainly been used as injectable scaffolds to treat small defects rather than patches for large ones.…”
Section: Introductionmentioning
confidence: 99%
“…RADA16 can induce cell differentiation itself (30,31). In this study, we evaluated the osteogenetic induction of gMSCs in the post-enriched SAP/DBM composite.…”
Section: Discussionmentioning
confidence: 99%